Determining The Depth of Hard Soil Layers Using Geoelectric Resistivity and Cone Penetration Test Methods (Case Study: Kelurahan Bontoramba Kecamatan Somba Opu Kabupaten Gowa) - Nurhasanah, Nurhasanah; Muhiddin, Achmad Bakri; Djamaluddin, Abdul Rahman; Niswar, Muhammad (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
Hard soil layers can impact the loading, stability, and behavior of structures in the geotechnical field. Comprehensive understanding of the depth and properties of hard soil layers can aid in designing suitable structures. Therefore, this study employed the resistivity geoelectric and Cone Penetration Test (CPT) methods to map the features of hard soil layers. Resistivity data were acquired through measurements utilizing the geoelectric method, while data on cone resistance, shear resistance, and friction ratio were gathered through field measurements using the CPT tool. The collected data was analyzed comprehensively to obtain a complete understanding of soil conditions. Based on resistivity values, the results indicated the research site comprises alluvium, very dry clay, and dry sandy soil. Based on the CPT test, it is determined that the layers contain mixtures of fine-grained soils, clay, silt, and sand. Therefore, it can be inferred that the dense sand lithology constitutes the hard soil layer geologically. The employment of both approaches delivers supplementary details on soil features and depth.